MEASUREMENTS OF WOMEN’S AUTONOMY IN REPRODUCTIVE HEALTH IN DEVELOPING COUNTRIES: A LITERATURE REVIEW: REPRODUCTIVE HEALTH - Yunita Amraeni; M. Nirwan (STIKes Mandala Waluya Kendari, 2022)
Background: The autonomy associated with the essence of decision-making in the field of reproductive health, including about fertility, pregnancy, and the utilization of health services. The research has shown that autonomy occurred in poor countries and growing. This literature is intended to explore autonomy measures and policies related to reproductive health programs. Methods: Review of the literature search some databases such as the Online Public Access Catalog (OPAC) and Pubmed Medical Center (PMC). Twenty-two articles that met the criteria for discussion included articles dominated by South and Southeast Asia and parts of Africa, as well as one European region. Most of the literature defines women's autonomy using theories from previous literature. Results: the study proves that there is a link between autonomy and utilization of health services, family planning and fertility. Autonomy measurement is done by using direct and indirect dimensions. Dimensions direct connect participation in decision making related to the economy, household and mobility. The other dimension is to assess women's attitudes toward domestic violence. Dimensions are indirectly related to proxies that affect women's status such as employment, education or media exposure. Conclusion: Potential policies and programs related to reproductive health in developing countries basically recommend the integration of women's empowerment in health programs.